2005
DOI: 10.1088/0305-4470/38/7/002
|View full text |Cite
|
Sign up to set email alerts
|

Persistence in systems with conserved order parameter

Abstract: We consider the low-temperature coarsening dynamics of a one-dimensional Ising ferromagnet with conserved Kawasaki-like dynamics in the domain representation. Domains diffuse with sizedependent diffusion constant, D(l) ∝ l γ with γ = −1. We generalize this model to arbitrary γ, and derive an expression for the domain density, N (t) ∼ t −φ with φ = 1/(2 − γ), using a scaling argument. We also investigate numerically the persistence exponent θ characterizing the power-law decay of the number, Np(t), of persisten… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The low temperature coarsening dynamics of the one-dimensional Ising ferromagnet with conserved Kawasaki-like dynamics was also studied in Ref. [155]. In these models, the domains of size l diffuse with a size-dependent diffusion constant D(l) ∝ l γ , with γ = −1.…”
Section: Coarsening With a Conserved Order Parametermentioning
confidence: 99%
See 2 more Smart Citations
“…The low temperature coarsening dynamics of the one-dimensional Ising ferromagnet with conserved Kawasaki-like dynamics was also studied in Ref. [155]. In these models, the domains of size l diffuse with a size-dependent diffusion constant D(l) ∝ l γ , with γ = −1.…”
Section: Coarsening With a Conserved Order Parametermentioning
confidence: 99%
“…In Ref. [155] the authors generalized the original model to arbitrary γ and, by using a scaling argument to compute the size distribution of domains, showed that the domain density decreases algebraically as N (t) ∼ t −1/(2−γ) . The persistence probability was shown, numerically, to decay as a power law as Q(t) ∼ t −θ , where θ depends on γ.…”
Section: Coarsening With a Conserved Order Parametermentioning
confidence: 99%
See 1 more Smart Citation
“…Persistence was also studied in various other contexts, including random walks and Gaussian processes [9,[38][39][40], fluctuating interfaces and surface growth [41][42][43][44][45][46][47], systems with shear flow [48][49][50], models with algebraic long-range interactions [51,52], and disordered systems [53][54][55][56]. Moreover, various authors have improved and generalized the concept of persistence in different ways [57][58][59][60][61][61][62][63][64][65][66][67][68]. Some predictions were confirmed experimentally and successfully applied to financial data [64,[69][70][71][72][73][74].…”
Section: Introductionmentioning
confidence: 99%
“…Measurements of persistence exponents in thin layers of twisted nematic liquid crystal, which provide a physical realization of a quenched thermodynamic system characterized by an Ising-like nonconserved order parameter have been carried out [13]. However, beyond computer simulations of Ising ferromagnets with conserved Kawasaki-like dynamics [14], no measurements of persistence were performed in coarsening systems characterized by conserved dynamics and controllable volume fraction [15].…”
mentioning
confidence: 99%